Nelson Island, Trinidad (2011)
Colour: Sepia; Style: Landscape; Other: Bordered, Undivided Nelson Island, one of the Five Islands which are located west of Port of Spain in the Gulf of Paria. The island was used as a disembarkation and quarantine station for indentured labourers, which included Chinese and Indian immigrants between 1866 and 1917. Funding for this project has been provided by Mrs. Irma E. Goldstraw.